PEMASARAN POLITIK LEGISLATIF PETAHANA DALAM MEMENANGKAN PEMILU ANGGOTA DPRD KOTA KUPANG PROVINSI NUSA TENGGARA TIMUR TAHUN 2009 (Kajian Strategi Politik dan Bauran Produk Politik) - VERONIKA, VERONIKA (Politika: Jurnal Ilmu Politik, 2012)
ABSTRACT In the reform era that demands a lot of changes, some incumbent legislators still adorned the face of House of Representatives of Kupang City. This was because the incumbent legislator already well known by electorate and there were no regulation before that confined the length of time a person nominated to be member of legislators whether in House of Representatives, House of Provincial Representatives, and House of Regency/City Representatives. Nevertheless, it was not guaranteed that incumbent legislator will be re-elected in the next period, because it depends on political marketing strategy that  used by incumbent legislator. The method used in this study was more qualitative-decriptive aimed to reveal the political marketing strategy and political product mixture to win  House of Kupang Regency Representatives legislative election in 2009. Analysis conducted relying on primary data obtained through secondary document review and in-depth interview with competent sources. Keyword: Political marketing strategy and political product mix, Incumbent Legislator  and  election.